Membangun Potensi Melalui Pendidikan Anak: Perspektif Ibnu Sina dalam Islam - Akmal, Miftahul Jannah; Arya Rahardja, Muhammad Nurfaizi; Syahidin, Syahidin; Fakhruddin, Agus (UIR Press, 2024)
Child education in Islam plays a crucial role in shaping the character and morality of individuals from an early age. This article aims to investigate the concept of child education in Islam from the perspective of Ibn Sina, a prominent scientist and philosopher in the 11th century. A descriptive-analytical method is employed to analyze Ibn Sina's concepts related to child education. The research findings reveal that Ibn Sina emphasizes education as a holistic journey involving the development of each child's unique potential. He views education not only as the transfer of knowledge but also as moral and spiritual guidance. Ibn Sina's contributions to child education include character development, balance between intellectual-moral-spiritual aspects, and the crucial role of educators as moral role models. In the Islamic context, child education encompasses not only religious aspects but also moral values forming the moral foundation for future generations. Ibn Sina's concepts weave Islamic values with philosophical thoughts, providing a broad dimension to the understanding of child education in Islam.